Systematic review and meta-analysis of the effectiveness of moxibustion therapy for primary dysmenorrhea - Song, ShiWei; Chen, Hao (Frontiers in Medicine, 2025)
BackgroundPrimary dysmenorrhea is a common gynecological disease. Compared with traditional Chinese medicine treatment, moxibustion has advantages as a main treatment method. Therefore, we conducted a systematic review and meta-analysis to evaluate the efficacy of simple moxibustion therapy for primary dysmenorrhea.MethodsRandomized controlled trials were searched from PubMed, Web of Science, Embase, The Cochrane Library, China National Knowledge Infrastructure, Wan-fang database and VIP database. In the literature included in these databases, clinical reporters evaluated the efficacy of moxibustion as the treatment for primary dysmenorrhea. All included literature was assessed for risk bias by using Risk of Bias assessment tool 2.0, and meta-analysis was conducted using Rev. Man 5.4.ResultsThe findings demonstrated that the moxibustion group exhibited a statistically significant response in comparison to the control group. The improvement observed in the Cox Menstrual Symptom Scale and the visual analogue scale score between the two groups exhibited heterogeneity, with a statistically significant difference noted. In terms of Traditional Chinese Medicine symptom scores, the experimental group demonstrated superiority over the control group. Furthermore, the progesterone levels in the moxibustion treatment were found to be higher than in the control group, while the estrogen levels in the experimental group were lower than in the control group, with a statistically significant difference observed (p < 0.05). Conversely, the levels of β-EP and PGE2 in the observation group were higher than those in the control group.ConclusionMoxibustion therapy shows significantly better efficacy in treating primary dysmenorrhea. However, a large sample, multi-center, high-quality RCT is still needed to evaluate its safety and efficacy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, Identifier CRD42024580466.